2022
DOI: 10.1111/cogs.13083
|View full text |Cite
|
Sign up to set email alerts
|

Embodied Space‐pitch Associations are Shaped by Language

Abstract: Height-pitch associations are claimed to be universal and independent of language, but this claim remains controversial. The present study sheds new light on this debate with a multimodal analysis of individual sound and melody descriptions obtained in an interactive communication paradigm with speakers of Dutch and Farsi. The findings reveal that, in contrast to Dutch speakers, Farsi speakers do not use a height-pitch metaphor consistently in speech. Both Dutch and Farsi speakers' co-speech gestures did revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…As such, investigating pitch metaphors provides a window on mental pitch representations. To illustrate, the Farsi language offers a low codability for pitch (Holler et al, 2022). Whereas, a pitch-thickness metaphor is commonly preferred, other expressions involving verticality can also be used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, investigating pitch metaphors provides a window on mental pitch representations. To illustrate, the Farsi language offers a low codability for pitch (Holler et al, 2022). Whereas, a pitch-thickness metaphor is commonly preferred, other expressions involving verticality can also be used.…”
Section: Discussionmentioning
confidence: 99%
“…To illustrate, tones are referred to as "thin" and "thick" in Turkish (Dolscheid et al, 2020) or "tight" and "loose" by the Kreung people Cambodja (Parkinson et al, 2012), to cite only two examples. Crucially, studies influenced by Cognitive Metaphor Theory (Zbikowski, 2002;Ashley, 2004;Shayan et al, 2011;Dolscheid et al, 2013Dolscheid et al, , 2020Casasanto, 2017;Cox, 2017;Fernandez-Prieto et al, 2017;Holler et al, 2022) propose that the way pitch qualities are coded in a language, shapes the way people conceive of pitch and vice versa. As such, pitch mappings become hard-wired during development because of the linguistic system and its conventional nature.…”
Section: Introductionmentioning
confidence: 99%
“…The saliency of verticality in language is also attested by the frequent usage of conceptual metaphors that express abstract ideas along the vertical dimension ( Lakoff and Johnson, 1999 , 2003 ; Gallese and Lakoff, 2005 ; Cian, 2017 ). In this regard, pitch is metaphorically conceptualized in the vertical space in most Western European languages and some non-Indo-European languages, with high pitch associated with upward movements and upper space, and low pitch associated with downward movements and lower space ( Eitan and Timmers, 2010 ; Clark et al, 2013 ; Fernandez-Prieto et al, 2017 ; Holler et al, 2022 ; see Walker et al, 2010 and Dolscheid et al, 2014 for evidence in prelinguistic infants, and Shayan et al, 2011 and Dolscheid et al, 2013 for thickness/pitch association in languages such as Farsi and Turkish). In a speeded pitch discrimination task, Rusconi et al (2006) revealed faster and more accurate responses to decide that tones where higher or lower in frequency than a reference tone when participants pressed an upper or lower key, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, these correspondences both manifest in languages, and can be intensified or fine-tuned by language learning (Holler et al 2022). Our capacity to make novel metaphors, and internalize them as conventions, is part of the same cross-modal cognitive suite underlying linguistic iconicity.…”
Section: Metaphormentioning
confidence: 99%